Spatial navigation in autism spectrum disorders: a critical review - Smith, Alastair D. (Frontiers in Psychology, 2015)
On the basis of relative strengths that have been attributed to the Autistic cognitive profile, it has been suggested by a number of theorists that people with Autism Spectrum Disorders (ASD) excel at spatial navigational tasks. However, many of these claims have been made in the absence of a close inspection of extant data in the scientific literature, let alone anecdotal reports of daily navigational experiences. The present review gathers together published studies that have attempted to explicitly address functional components of navigation in ASD populations, including assays of wayfinding, large-scale search, and path integration. This inspection reveals a pattern of apparent strengths and weaknesses in navigational abilities, thus illustrating the necessity for a more measured and comprehensive approach to the understanding of spatial behaviour in ASD.